The Flemish and German Nation of Seville: Collective Strategies and Institutional Development of the Northern European Merchant Community in Seville, Spain (1568-1598) - Jiménez Montes, Germán (TSEG - The Low Countries Journal of Social and Economic History, 2022)
This article studies how northern European migrants adapted their collective strategies to Seville’s institutional framework in the last third of the sixteenth century and how these strategies shaped the emergence of the so-called Flemish and German nation. It analyzes the group’s motivations to refuse the creation of a particularized commercial institution, as well as the alternative institutional mechanisms they developed to organize themselves in southern Spain. The article sheds light on the role of open-access institutions in Spain to facilitate long-distance trade and gives a new insight into the evolution of the commercial connections between the Spanish monarchy and the Dutch Republic during the Eighty Years’ War.